INFLUENCE OF THE PROJECT “QUALITATIVE INCLUSIVE EDUCATION FOR SPECIAL NEEDS CHILDREN” ON THE DEVELOPMENT OF INCLUSIVE EDUCATION IN THE PROJECT SCHOOLS - Nīmante, Dita; Daniela, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The study „Evaluation of the project influence on the development of inclusive education in project schools” was implemented from 2009 till 2011 in the project “Qualitative inclusive education for special needs children” (Education initiative centre, State Education content centre, Soros Foundation Latvia, more information in: http://www.iic.lv) with the aim to find out whether the project results brought changes in defined inclusive education indicators. The article analyzes how the cooperation of school’s pedagogues in promoting inclusive education in general comprehensive school has improved as a result of the project.